Surgical Stabilization for Post-Operative Discitis Patients Concerning Pain Relief and Functional Outcomes - Abdul Sattar; Samir Khan Kabir; Muhammad Zahid Khan; Muhammad Waqar Khan; Muhammad Arif Khan (Gandhara University, 2023)
OBJECTIVES This study evaluated pain relief and functional outcomes in patients who underwent surgical stabilization following post-operative discitis. METHODOLOGY A cross-sectional was conducted at the Department of Orthopedic and Spine Surgery, Peshawar. The study duration spanned from 2020-2023. The inclusion criteria for participants involved patients who had experienced post-operative discitis and subsequently underwent surgical stabilization, with a stipulated minimum follow-up period of two weeks. Pain relief was measured using the Visual Analogue Score (VAS) for back and leg pain, while functional outcomes were evaluated using the Oswestry Disability Index (ODI). The acquired data were subjected to analysis utilizing SPSS version 26.0. RESULTS Out of the 35, 51.4% were male, and 48.6% were female, with a mean age of 47.5 years (SD ± 10.9 years). The most frequently affected lumbar spine level was L4-L5 in 57.1% of patients. 31.4% were smokers, and 45.7% had comorbidities, primarily consisting of diabetes or hypertension. Significant improvements were observed for back pain (baseline: 9.29 ± 0.71, post-stabilization: 5.37 ± 1.47, p = 0.001) and leg pain (baseline: 3.32 ± 2.17, post-stabilization: 1.91 ± 1.02, p = 0.001). Functional outcomes also showed substantial recovery (baseline: 51.57 ± 6.91, post-stabilization: 34.89 ± 6.85, p = 0.001). Preoperatively, the patients exhibited a spectrum of disability levels, with 29% experiencing severe disability. After two weeks of surgical intervention, substantial improvement was noted, 6% had severe disability. At the last follow-up, only 1% remained severely disabled, underlining the significant enhancement in functional outcomes post-stabilization. CONCLUSION Surgical stabilization is associated with significant pain relief and improved functional outcomes in patients with post-operative discitis.